Invasive Pneumococcal Disease in a Population with Underlying Comorbidities. (4th October 2017) - Jarovsky, Daniel; Berezin, Eitan Naaman; De Almeida, Rodrigo José Sini
Abstract: Background: Streptococcus pneumoniae ( Spn) is a major cause of severe and life-threatening diseases in children and particularly among individual with high-risk illnesses at all ages. As there is limited clinical data on IPD in high-risk patients and indirect effect of vaccination in the post-PCV10 era in developing countries, we´ve assessed the epidemiology of IPD in patients with and without selected underlying diseases before and after PCV10 introduction at Santa Casa de São Paulo (SCSP), Brazil. Methods: We´ve performed a prospective hospital-based surveillance study of patients with IPD from January 2000 to April 2017, including all cases of IPD (i.e isolation of Spn from a normally sterile body fluid) among patients at all ages. Selected cases were stratified into 5 age groups to evaluate comorbidities and the effect of the PCV10 on different ages. Identified serotypes were grouped according to the available pneumococcal vaccines and further analyzed into pre-vaccination (2000–2009) and post-vaccination periods (2010–2017). Clinical information was extracted from patient´s records, then stratified based on their IPD risk profile. Ethical approvals to conduct the study were obtained from the SCSP institutional review board. Results: 571 episodes were identified in 561 patients in all age groups, of which 440 (78.4%) had clinical data for analysis: 20.7% healthy; 79.3% had comorbidities. IPD decreased from 35.9 to 30.3 cases/year (-15.6%) at all ages after PCV10 introduction. Among healthy individuals and those with underlying comorbidities, annual cases changed from 6.8 to 2.9 (57.3% reduction) and 18.6 to 20.5 cases/year (9.7% increase), respectively, between same periods; 30-day mortality through pre-vaccine period was 25% and 7.5% and in post-PCV10 period 27% and 8.7%, for comorbidity and healthy groups, respectively. IPD significantly decreased among healthy and comorbidity children <5y, without evidence of serotype replacement. Significant increase in bacteremia and pneumonia, also in serotypes included in all vaccines and NVT was evidenced at ages over 5y. Conclusion: High rates of IPD have persisted in older subjects and in patients with established risk factors for IPD, despite children vaccination with PCV10. No herd effect was detected and serotype replacement is ongoing in this specific groups. Disclosures: E. N. Berezin, Pfizer: Grant Investigator, Educational grant; R. José Sini De Almeida, Pfizer Inc: Employee, Salary